Analysis Homestay Management During Covid-19 Pandemic in Kebangsaan Tourism Village Wonorejo - Gusriza, Fondina; Agni Andrea, Garsione; Muammar Alawi, A. (Publisher Cv. Inara, 2023)
This study aims to analyze the homestay management during the covid-19 pandemic in the Kebangsaan Tourism Village Wonorejo. The existence of homestays is very important to support tourist activities, such as extending the length of stay of tourists. Homestay was developed from 2017 and continues to increase and has an impact on the local economy. Since the COVID-19 pandemic, management has implemented health protocols in accordance with government recommendations. Therefore, it is necessary to analyze the management of homestays during the covid-19 pandemic. This research was conducted with a descriptive-qualitative approach. The data analysis technique used the POAC management theory (planning, organizing, actuating, and controlling) to obtain the results of homestay management during the Covid-19 pandemic in the application of CHSE. The results of the study show that the management of homestays in the Kebangsaan Tourism Village during the Covid-19 pandemic has not implemented CHSE. Some have taken basic infection prevention measures such as encouraging frequent hand washing, providing hand sanitizer, urging employees to stay home if they are sick, preparing extra tissues and trash containers in public areas, increasing time in room maintenance. In addition, several managements have also implemented hygiene and environmental safety, such as: cleaning surfaces that look dirty followed by disinfection and performing additional cleaning on all frequently touched areas. Management has not implemented social distancing. Management needs training and socialization in implementing CHSE for homestay management.